(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This research examines how personality qualities and socioeconomic circumstances affect stress levels and stress-related symptoms in challenging-job workers. The study included 34 psychiatric nurses. Women made up 68% of the sample and averaged 35.18 years old, while men averaged 32.25. The study examined how gender, age, and work tenure affected stress and symptoms, as well as how personality characteristics and stress interacted. The research found that female nurses’ stress increased with age and service, whereas male nurses’ stress increased at the start of their employment. Personality factors correlated strongly with stress and its effects. Researchers found that socioeconomic pressures affected individuals with poor social presence, empathy, independence, and intellectual efficiency. Less psychological insight, career direction, tolerance, and well-being were linked to more severe stress symptoms. These people were also more feminine. These results show that gender variations in stress adaptation are considerable and that personality traits mitigate socioeconomic stresses. This research emphasizes personalized mental health therapy and social support. These methods should consider participants’ socioeconomic status and personality.Socioeconomic Stressors